Performance of Cabbage Genotypes as Influenced by Bio-Fertilizers and Nitrogen Doses - A.D. SHARMA; S.K. YADAV; B.S. MEHTA (Seed Research, 2026)
Golden Acre was found earliest to harvest, whereas Pusa Mukta excelled in respect of net weight of head and yield attributes over others out of the three cabbage cultivars (Pride of India, Golden Acre and Pusa Mukta) tested in the present studies. The combined use of nitrogen and Azospirillum proved to be the most effective treatment for the enhancement of net weight and yield of cabbage heads.